2011
DOI: 10.1209/0295-5075/96/25001
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of zonal flows on wave turbulence driven by small-scale instability in the Charney-Hasegawa-Mima model

Abstract: We demonstrate theoretically and numerically the zonal-flow/drift-wave feedback mechanism in an idealised 2-dimensional model of plasma turbulence driven by a small-scale instability. Zonal flows are generated by a secondary modulational instability of the modes which are directly driven by the primary instability. The zonal flows then suppress the small scales thereby arresting the energy injection into the system, a process which can be described using nonlocal (in scale) wave turbulence theory. Finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…Theories of stratified wave turbulence should take these effects into account. The mechanism, and the tools presented here, can be also relevant in quasi-geostrophic turbulence [33] and plasma turbulence [34,35], where zonal flows are also known to develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theories of stratified wave turbulence should take these effects into account. The mechanism, and the tools presented here, can be also relevant in quasi-geostrophic turbulence [33] and plasma turbulence [34,35], where zonal flows are also known to develop.…”
Section: Discussionmentioning
confidence: 99%
“…While this theory can give information on the formation of the nonlinear energy cascade, it cannot characterize interactions of the wave field with a mean flow. Some extensions that consider nonlocal interactions and the development of zonal flows have been proposed to address this, and are specially relevant in the context of quasi-geostrophic turbulence [33], and plasma turbulence in tokamaks [34,35] to explain the development of large-scale flows.…”
Section: Introductionmentioning
confidence: 99%
“…We find that this transfer is mostly anisotropic and mostly to the zonal component. It is possible that a negative feedback loop forms, similar to in the one-layer model (Connaughton et al, 2011), whereby the growth of large scales should turn off the energy source (which we showed in the case of WT cannot be BI). One can answer this by direct numerical simulation (DNS) of the two-layer model and this is something to consider in future work.…”
Section: Resultsmentioning
confidence: 67%
“…It was claimed by these authors that the original HW model does not predict the formation of ZFs, which appears to be in contradiction with the CHM results of Connaughton et al and reported in Ref. [34], considering the fact that the HW model includes the CHM model as a limiting case. We discuss here the importance of addressing the problem of drift-wave turbulence in the framework of the reduced Hamiltonian model for trapped particles, in order to gain a better understanding of the differences between the HW and MHW models.…”
Section: Applications To Chm and Hw Turbulencementioning
confidence: 57%